Optimización de tiempos y movimientos del trabajador en los procesos agrícolas de la empresa Nintanga S.A. - Tovar Tobar, Holguer Fabián (2019)
The company NINTANGA S.A against the current changes that the world demands, needs methodologies which approve to generate information starting from the inquiry and the development related with the times optimization in their agricultural activities, this shall facilitate them the survival in a high competitive environment, being as this shall allow them to compare what they have, against what it is demanded, and consequently they will be able to response accurately to their customers. The present project focuses in analyzing the company agro-productive processes and purpose improvement alternatives in the agriculture activities, of transplant, fertilization and harvest of the different products that the company offers, in this manner will reduce the production costs and will increase the workers efficiency. Also, the percentage of workers' nonproduction times will gradually reduce. In the part of study of times and movements consists of a series of different procedures for the description and technical scientific analysis of work methods that the laborer must adapt in order to accomplish the task or assigned activity. The production costs are stablished through the used resources at a given level of optimization, and as a result when the productivity increase, the workforce costs decrease in every agricultural activity that the workers do. The study of initial situation, gave us an approach of all the flaws and deficient times in the activities previously mentioned, through the diagram process all the productive and nonproductive elements were analyzed in which the operations could have setbacks and delays. For the optimization of resources it is plant an improvement plan which will generate a higher profit to the company with the same staff.